Undisclosed antiretroviral drug use in a multinational clinical trial (HIV prevention trials network 052) - Jessica M. Fogel (2018)
The HIV Prevention Trials Network 052 study enrolled serodiscordant couples. Index participants infected with human immunodeficiency virus reported no prior antiretroviral (ARV) treatment at enrollment. ARV drug testing was performed retrospectively using enrollment samples from a subset of index participants. ARV drugs were detected in 45 of 96 participants (46.9%) with an undetectable viral load, 2 of 48 (4.2%) with a low viral load, and 1 of 65 (1.5%) with a high viral load (P < .0001); they were also detected in follow-up samples from participants who were not receiving study-administered treatment. ARV drug testing may be useful in addition to selfreport of ARV drug use in some clinical trial settings. © The Author 2013. Published by Oxford University Press on behalf of the Infectious Diseases Society of America. All rights reserved.